Albatredines A and B, a pair of epimers with unusual natural heterocyclic skeletons from edible mushroom Albatrellus confluens. Issue 42 (2nd July 2018) - Zhang, Shuaibing; Huang, Ying; He, Shijun; Chen, Heping; Li, Zhenghui; Wu, Bin; Zuo, Jianping; Feng, Tao; Liu, Jikai
Abstract : A chemical study of the common species Albatrellus confluens present in Yunnan province, southwest China led to the identification of a pair of epimers named albatredines A (1 ) and B (2 ). Abstract : A chemical study of the common species Albatrellus confluens present in Yunnan province, southwest China led to the identification of a pair of epimers named albatredines A (1 ) and B (2 ). They feature a natural unprecedented 1, 2, 4-oxadiazolidin-5-one skeleton. The acyl substitution pattern and complete configurational assignments were deduced from the comparison between experimental and theoretical 13 C NMR and ECD data, respectively. Bioassay results showed that compound1 exhibited a weak immunosuppressive activity against the concanavalin A-induced T lymphocyte cell proliferation (IC50 2.99 μM).